A Patient with Typhoid Hepatitis - M Vitanata Arfijanto; Isty Rindryastuti (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Typhoid hepatitis is typhoid fever accompanied by symptoms of jaundice, hepatomegaly and abnormal liver function tests. The incidence varies between 0.4% -26% of typhoid fever patients. We report a case of a 34-year-old male, presented with fever, epistaxis, gastrointestinal symptoms, thrombocytopenia and elevated AST/ ALT, thus the patient was first diagnosed as dengue hemorrhagic fever grade II. On day 9th the signs and symptoms were persisted, Ig M and Ig G Dengue was negative. Then we evaluated the virus marker for hepatitis and blood culture. The results were negative for HBsAg, anti HCV and Ig M anti HAV, but Salmonella typhi detected on blood culture. The patient was treated with ceftriaxone 1000mg bid iv and get better then discharged from hospital.